Untellable tales and uncertain futures: the unfolding narratives of young adults with cancer. Issue 4 (3rd July 2020) - Pearce, Susie; Gibson, Faith; Whelan, Jeremy; Kelly, Daniel
ABSTRACT: In this paper, we examine the use of creative methods for understanding the experience of young adults aged between 16 and 30 years over a year following a cancer diagnosis. Exploring the renegotiation of identity, the narrative, longitudinal research design of the study demonstrated the unfolding process of the narrative work between participants and researcher. We used a combination of visual, spoken and reflexive psychosocial approaches to understand emergent narratives, many of which do not always find symbolisation in language. Our methodological approach focused on the difficult and sometimes 'unspeakable' nature of the young adults' narratives, demonstrating the importance of different modes of communication in articulating complicated relations with uncertain futures. In this respect the links between narrative, social action and the imagining of possible futures are precarious. In this paper, we explore how untellable issues were explored, and the challenges of doing so.